Analysis of business development using a business model canvas approach - Ratna Ningsih; Fanji Wijaya; Erna Herlinawati (Junal Ilmu Manajemen, 2023)
The purpose of this study is to analyze the development business with Business Model Canvases approach of Carita Weddings Organizer at Bandung. The method of this study used descriptive qualitative method. Process acquisition data conducted with interviewed with owner and employee Carita Weddings Organizer. The results of this study proved that Carita Weddings Organizer already own framework nine element Business Model Canvases (BMC) which becomes reference in operate business, however there is still lack in optimizing BMC which where researcher adopt analysis SWOT (Strengths, Weaknesses, Opportunities, and Threats) for analyze development business with approach business Model Canvases of Carita Weddings Organizer at Bandung.